CONSUMER PREFERENCES IN DONUT SHOP USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (Case Study: Dolphin Donuts, Dunkin’ Donuts Mantos and J.Co Megamall) - Lasut, Nanhito Clary; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (FEB Universitas Sam Ratulangi Manado, 2021)
In this study, the researcher will examine the snacks as well as a place to gather with friends, especially types of snacks, donuts. Manado has 3 donut shops namely Dolphin Donuts, Dunkin Donuts Mantos, and J.Co Megamall. There are many factors or criteria that influence the consumer to go to a donut shop. The method used in this research is Analytical Hierarchy Process (AHP). AHP is a method for ranking decision alternatives and selecting the best one given multiple criteria. Based on six criteria (cleanliness, food quality, price, physical environment, service quality, and location), there are the top three criteria that have the most influence on a consumer of a donut shop in Manado city which is cleanliness, food quality, and physical environment. Every donut shop in Manado needs to pay attention seriously to these three factors. Based on the overall result, shows that J.Co Megamall becomes the most preferred donut shop in Manado City. Dolphin Donuts has the lowest score. Dolphin Donuts should improve the cleanliness, food quality, and physical environment of the restaurant, make the customers feel comfortable when they gathering with family or friends.Â Keywords: consumer preferences, analytical hierarchy process